1999
DOI: 10.1002/(sici)1098-2396(199904)32:1<58::aid-syn8>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone regulation of serotonin transporter and 5‐HT1A receptor expression in the aging brain

Abstract: Hypercortisolemia is often observed in patients suffering from major depression. As the serotonergic (5-hydroxytryptamine; 5-HT) system plays a major role in the etiology of depression, a loss of endocrine and neurotransmitter system interactions, including corticosterone regulation of 5-HT transporter (5-HTT) and 5-HT receptor expression, may underlie age-related deficits in the regulation of the hypothalamic-pituitary-adrenal (HPA) axis and correlate with an increased incidence of depression with advancing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The binding of [ 3 H] paroxetine to cortical SERT was unaffected by current or previous corticosterone treatment. This is in agreement with two previous reports showing that neither infusion of a high level of corticosterone (600 mg corticosterone in a 21‐day implant) (37) nor dexamethasone (60 µg/kg/day for 26 days) (38) alter cortical SERT binding in 3‐month‐old rats. Furthermore, even in the hippocampus where there have been several studies, glucocorticoids only appear to affect SERT levels when administered to rats aged less than 3 months (43–47), which is consistent with the current observation.…”
Section: Discussionsupporting
confidence: 93%
“…The binding of [ 3 H] paroxetine to cortical SERT was unaffected by current or previous corticosterone treatment. This is in agreement with two previous reports showing that neither infusion of a high level of corticosterone (600 mg corticosterone in a 21‐day implant) (37) nor dexamethasone (60 µg/kg/day for 26 days) (38) alter cortical SERT binding in 3‐month‐old rats. Furthermore, even in the hippocampus where there have been several studies, glucocorticoids only appear to affect SERT levels when administered to rats aged less than 3 months (43–47), which is consistent with the current observation.…”
Section: Discussionsupporting
confidence: 93%
“…5-HT 1A receptors are also down-regulated in the DRN following uncontrollable shock (Short, 2000) and a repeated stress paradigm (Lanfumey et al, 1999). Consistent with these data, the chronic administration of the stress hormone corticosterone (Fernandes et al, 1997; Kuroda et al, 1992; Takao et al, 1997) or the synthetic glucocorticoid dexamethasone (Katagiri et al, 2001; Lanfumey et al, 1999) has been shown to increase the density and function of cortical 5-HT 2A receptors, while at the same time decreasing the density of 5-HT 1A receptors in frontal cortex (Crayton et al, 1996) and hippocampus (Fernandes et al, 1997; Maines et al, 1999; Takao et al, 1997). Together, these data suggest that chronic stress could shift the balance of BNST 5-HT responses to favor excitation, so that the stress-induced release of 5-HT would produce an anxiogenic response.…”
Section: Modulation Of the Serotonin Response In Bnst Neuronsmentioning
confidence: 67%
“…Several treatments have been shown to alter the functional expression of 5-HT receptor subtypes in other brain regions, including chronic stress (Ferretti et al, 1995; Lanfumey et al, 1999; Lopez et al, 1998; Lopez et al, 1999; McKittrick et al, 1995; Ossowska et al, 2001; Takao et al, 1997), treatment with stress hormones (Crayton et al, 1996; Fernandes et al, 1997; Ferretti et al, 1995; Katagiri et al, 2001; Kuroda et al, 1992; Maines et al, 1999; Takao et al, 1997), antidepressant treatment (Elena Castro et al, 2003; Gurevich et al, 1993; Hanson et al, 1998; Lund et al, 1992; Riad et al, 2004; Strome et al, 2005), and voluntary exercise (Greenwood et al, 2005). …”
Section: Modulation Of the Serotonin Response In Bnst Neuronsmentioning
confidence: 99%
“…However, treatments such as chronic stress or the chronic administration of stress hormones have been shown to decrease 5-HT 1A and/or increase 5-HT 2A receptors in other brain regions (Kuroda et al, 1992, Ferretti et al, 1995, McKittrick et al, 1995, Crayton et al, 1996, Fernandes et al, 1997, Takao et al, 1997, Lopez et al, 1998, Lanfumey et al, 1999, Lopez et al, 1999, Maines et al, 1999, Katagiri et al, 2001, Ossowska et al, 2001). A reduction in BNST ALG 5-HT 1A receptor activity and/or and increase 5-HT 2A receptor activity would favor an anxiogenic role of BNST ALG 5-HT release, and could disrupt the normally anxiolytic role of 5-HT and produce a behavioral state characterized by pathological anxiety.…”
Section: Discussionmentioning
confidence: 99%